Expansão urbana e vulnerabilidades sócioambientais no distrito sede de Senador Canedo-GO 2008 – 2018 - Martins, Antonio Henrique Capuzzo (2019)
The present study aims to analyze the history of urban evolution of the municipality of Senador Canedo, state of Goiás - Brazil, observing the real conditions, implications and weaknesses triggered in the last 10 years (2008 - 2018). Inserted in the Metropolitan Region of Goiânia (RMG), the hypothesis of this thesis is that the urban expansion of the municipality, directly linked to the growth of Goiânia, occurred quickly, accelerated and without order, which favored the production of a series of institutional vulnerabilities. , social and environmental. To this end, we used the methodology proposed by Zuquette (1987), which proposes to analyze and evaluate attributes of the physical environment and their behavior from different forms of occupation aiming to guide conditions for planning and occupation in order to assist in the mitigation of problems in courses and possible future impasses in irregular or inadequate occupation in urban centers. This paper is divided into five chapters, as well as introduction, concluding remarks, references and annexes. The first part presents a literature review, that is, a theoretical-conceptual discussion around the concepts of territory; urban gaps and vulnerabilities. Chapters 2 and 3 have the function of spatializing the area of localization of the phenomenon, thus, chapters characterize the formation of the RMG and the municipality of Senador Canedo, respectively. The fourth section of the thesis has the function of presenting the proposed methodology for the work as well as the environmental indicators used in the geotechnical mapping of the area. The last chapter of the thesis shows the vulnerabilities found in the municipality, highlighting the irregularities and urban voids arising from the recent expansion of the city. The results show a process of urban dispersion in the RGM; technical and political weaknesses and a marginalization of the population living in the most remote neighborhoods of the urban center, which lives in precarious situations after the intense financialization experienced by the country in the last decade that is characterized by the possibility of owning a house even if there are no minimum conditions of habitation. and quality of life.